Intervista al GEN. B. Mariano MOSSA, Comandante Carabinieri Tutela Patrimonio Culturale - Papi, Luca; Guidi, Paola (Archeomatica, 2014)
In the framework of the cultural heritage, several records are recognized to our Country. With regard to them, it is worth to mention the establishment of a selected body of investigators Carabinieri Tutela Patrimonio Culturale specifically dedicated to combating crimes against cultural heritage. The Interview to Gen. B. Mariano Mossa is mainly focused to highlight the experience gained over more than 40 years of activity by the mentioned body. In particular, it will be illustrated the features and services which can enjoy a citizen by downloading the mobile app developed by Carabinieri Tutela Patrimonio Culturale.